Phosphoric Acid-Doped Ion-Pair Coordinated PEMs with Broad Relative Humidity Tolerance - Ding Tian; Taoli Gu; Sai Nitin Yellamilli; Chulsung Bae (Energies, 2020)
Proton exchange membrane (PEM) capable of working over a broad operating condition window is critical for successful adoption of PEM-based electrochemical devices. In this work, phosphoric acid (PA)-doped biphenyl-backbone ion-pair coordinated PEMs were prepared by quaternization of BPBr-100, a precursor polymer, with three different tertiary amines including trimethylamine, 1-methylpiperidine, and 1,2-dimethylimidazole followed by membrane casting, ion exchange reaction to hydroxide ion, and doping with PA. The resulting PA-doped ion-pair PEMs were characterized in terms of PA doping level, proton conductivity, relative humidity (RH) tolerance, thermal stability, and mechanical properties. PA doping levels were between six and eight according to acid-base titration. The size and structure of the cation group of ion-pair polymers were found to affect the PA doping level and water uptake. Proton conductivity was studied as a function of RH over a wide range of 5% to 95% RH. Stable conductivity at 80 °C was observed up to 70% RH for 10 h. Mechanical property characterization indicates that the PA doping process resulted in more ductile membranes with significantly increased elongation at break due to the plasticization effect of PA. A combination of high proton conductivity at low RH conditions, and good humidity tolerance makes this new class of PEMs great potential candidates for use in electrochemical devices such as proton exchange membrane fuel cells and electrochemical hydrogen compressors.